Advances in Recycling Technologies of Critical Metals and Resources from Cathodes and Anodes in Spent Lithium-Ion Batteries - Shuwen Wang; Yanrong Lai; Jingran Yang; Jiaxue Zhao; Yushan Zhang; Miaoling Chen; Jinfeng Tang; Junhua Xu; Minhua Su (Separations)
With the rapid economic development and the continuous growth in the demand for new energy vehicles and energy storage systems, a significant number of waste lithium-ion batteries are expected to enter the market in the future. Effectively managing the processing and recycling of these batteries to minimize environmental pollution is a major challenge currently facing the lithium-ion battery industry. This paper analyzes and compares the recycling strategies for different components of lithium-ion batteries, providing a summary of the main types of batteries, existing technologies at various pre-treatment stages, and recycling techniques for valuable resources such as heavy metals and graphite. Currently, pyrometallurgy and hydrometallurgy processes have matured; however, their high energy consumption and pollution levels conflict with the principles of the current green economy. As a result, innovative technologies have emerged, aiming to reduce energy consumption while achieving high recovery rates and minimizing the environmental impact. Nevertheless, most of these technologies are currently limited to the laboratory scale and are not yet suitable for large-scale application.